Analyzing the Impact of Technological Innovations on Smallholder Farmers Within Ivory Coast’s Cocoa Supply Chain - Letícia Souza Pereira (Law and Economy, 2024)
The integration of technology in Ivory Coast’s cocoa sector offers a transformative potential to enhance agricultural productivity, environmental sustainability, and the socio-economic well-being of smallholder farmers. This paper explores the impact of technological innovations, such as precision agriculture, improved cocoa varieties, mobile market platforms, and sustainable farming practices, on cocoa farming in Ivory Coast. Through case studies and analyses, the research highlights the benefits of technology in increasing yields, improving market access, and promoting sustainable cultivation methods. However, challenges such as accessibility, affordability, and the digital divide persist, necessitating comprehensive policy support, investments in infrastructure, and educational programs to ensure equitable benefits. The collaborative efforts of stakeholders, including the government, private sector, and international organizations, are crucial in creating an enabling environment for the adoption of technology in cocoa farming. This paper concludes that embracing technological advancements, while addressing existing barriers, is pivotal for the future sustainability and prosperity of Ivory Coast’s cocoa sector.